2015
DOI: 10.1530/rep-14-0549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal n-3 fatty acid supplementation on placental cytokines, pro-resolving lipid mediators and their precursors

Abstract: The aim of this study was to determine whether supplementation with fish oil-derived n-3 polyunsaturated fatty acids (n-3 PUFA) during pregnancy modifies placental PUFA composition, the accumulation of specialised pro-resolving lipid mediators (SPMs, specifically resolvins (Rv), protectins (PD) and upstream precursors) and inflammatory gene expression. Placentas were collected from women (nZ51) enrolled in a randomised, placebo controlled trial of n-3 PUFA supplementation from 20-week gestation. Lipids were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 43 publications
2
78
0
1
Order By: Relevance
“…Placental RvD2 levels increased in mid- and late-pregnancy, whereas PD1, RvD1, and 17R-RvD1 were only increased in late pregnancy [26]. This study corroborates with the findings in human placental tissue described above [25] and supports the hypothesis that maternal omega-3 PUFA supplementation increases placental levels of SPM and SPM precursors, which could result in enhanced ability to modulate or resolve inflammation. Furthermore, while these studies highlight the placenta as a site for production or utilization of SPM, the mechanism for utilization, production, and/or transport of SPM by the placenta is still largely unexplored.…”
Section: Literature Reviewsupporting
confidence: 86%
See 3 more Smart Citations
“…Placental RvD2 levels increased in mid- and late-pregnancy, whereas PD1, RvD1, and 17R-RvD1 were only increased in late pregnancy [26]. This study corroborates with the findings in human placental tissue described above [25] and supports the hypothesis that maternal omega-3 PUFA supplementation increases placental levels of SPM and SPM precursors, which could result in enhanced ability to modulate or resolve inflammation. Furthermore, while these studies highlight the placenta as a site for production or utilization of SPM, the mechanism for utilization, production, and/or transport of SPM by the placenta is still largely unexplored.…”
Section: Literature Reviewsupporting
confidence: 86%
“…A study by Keelan et al [25] assessed whether omega-3 supplementation during pregnancy modifies the fatty acid composition in the placenta and inflammatory gene expression, including transcripts for TNF-α, IL-1β, and IL-6. In placental tissue, it was found that omega-3 and omega-6 LC-PUFA, SPM precursors, and SPM are present in measurable quantities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few data attesting to their formation in humans based on rigorous mass spectrometric methodology. Most clinical investigations reporting the formation of SPMs rely on immunoassays ( 21 ) or MS without synthetic internal standards structurally similar to the SPMs under investigation (22)(23)(24)(25)(26)(27)(29)(30)(31)(32), often in ex vivo stimulated systems ( 17,(33)(34)(35)(36).…”
Section: Blood (Rbc Membranes) For the Study High Doses Of Lovaza Fishmentioning
confidence: 99%